An analysis of retinal gene therapy clinical trials. - Maclaren, R (2009)
In 2008, the initial results from the first three gene therapy trials to use adeno-associated viral vectors to treat an inherited retinal degeneration were published. These trials demonstrated no significant vector-related side effects and provided evidence of successful gene transfer with improved vision in several patients. The success of these trials heralds the beginning of a new era in the treatment of retinal diseases. Much can be learnt by comparing the results of the individual studies, as each has subtle differences, both in surgical technique and vector design. In contrast to laboratory models, humans generally have missense rather than null mutations and are treated later in the disease process than experimental models, when recipient cells are compromised. Intracellular stress responses, such as those regulated by endoplasmic reticulum protein kinase (PERK) and the mTOR pathways, are likely to inhibit the translation of transgenic mRNA by mechanisms that are not evident in null laboratory models treated early in the disease process. Understanding methods to overcome stress responses is likely to be a critical step in translating the applications of gene therapy from animal models to other human retinal diseases.